Immigrant Educators and Students' Academic Achievement - Kelvin Seah (Institute for the Study of Labor (IZA), 2016)
Using a dataset which allows students to be linked to their teachers, this paper examines how educators with an immigrant background affect the academic achievements of secondary school students in the United States. To account for the possibility that immigrant and native teachers may be assigned to different types of schools, and even within schools, to different types of students, two estimation strategies are employed. The first estimates the immigrant teacher impact by comparing the achievements of students with immigrant teachers to the achievements of observationally similar students with native teachers, within schools. The second compares the achievement of a student with an immigrant teacher in one subject to the achievement of the same student with a native teacher in another subject. The results suggest that, overall, immigrant teachers do not have a negative impact on the educational achievements of native students. Additional tests suggest that this non-adverse effect is due to the greater effectiveness of White immigrant teachers relative to native teachers.
Keywords: I21; J15; J61; 330; education economics; immigrant teacher; academic achievement